Library and Information Science Research in Asia-Oceania : theory and practice - Du, Jia Tina, 1981- editor; Zhu, Qinghua, 1963- editor; Koronios, Andy, 1954- editor (Hershey, Pennsylvania : Information Science Reference, 2014)
"This book presents evolving and emerging research and development in the field of library and information science (LIS) in diverse countries in Asia-Oceania as the region continues to develop"--provided by publisher.